Clinical progression and genetic pathways in body-first and brain-first Parkinson’s disease - Massimiliano Passaretti; Daniel Veréb; Mite Mijalkov; Yu-Wei Chang; Hang Zhao; Blanca Zufiria-Gerbolés; Jiawei Sun; Giovanni Volpe; Natalia Rivera; Matteo Bologna; Joana B. Pereira (Molecular Neurodegeneration)
Abstract Background Parkinson’s disease (PD) is a highly heterogeneous disorder with distinct phenotypes that can develop well before motor symptoms appear. Recently, two main phenotypes based on the different pathological spreading patterns of PD have been proposed: “body-first”, where α-synuclein pathology begins in the peripheral nervous system and spreads symmetrically from bottom-up, and “brain-first”, where pathology starts in the brain and spreads asymmetrically downwards. However, no studies have assessed these phenotypes across both prodromal and clinical PD stages, tracked their pathological progression in vivo or identified potential underlying biological mechanisms. Methods To address this, we analyzed 910 prodromal and 1120 clinical PD cases with comprehensive longitudinal clinical, imaging, and genetic data from the Parkinson Progression Marker Initiative over a 12-year period. Results Our findings revealed that both prodromal and clinical groups with body-first symptoms exhibited greater motor dysfunction, anxiety, and depression at baseline; as well as worse longitudinal motor progression and attention decline compared to brain-first cases. The body-first and brain-first phenotypes were stable over time and predicted conversion to clinical PD in prodromal cases, and were also found using unsupervised deep learning analyses. Additionally, body-first cases displayed more pronounced changes in the caudal LC, as well as symmetrical alterations in the striatum and glymphatic system, consistent with the traditional bottom-up progression described by Braak’s staging of α-synuclein pathology and the more symmetric distribution proposed for body-first PD. In contrast, brain-first cases exhibited changes in the rostral LC and asymmetric alterations in the striatum and glymphatic system, suggesting a top-down progression. Genetic analysis also identified new specific single nucleotide polymorphisms associated with PD phenotypes, such as TRIM40 and IP6K2, linked to worse motor and cognitive outcomes in prodromal cases. Conclusions These findings emphasize the importance of recognizing body-first and brain-first PD as distinct entities with unique clinical, imaging, and genetic profiles, paving the way for targeted and personalized therapeutic strategies that address the specific pathophysiological mechanisms of PD.